Abandoning Representations: Holocaust Imageries in Late Israeli Art Music. Issue 1 (2nd January 2016) - Shelleg, Assaf
Abstract : Discussing mechanisms of representation in modern Jewish art music in general and post-Holocaust commemoration music in particular, the article examines the dilution of musical signs in Holocaust-related works penned by Israeli composers Noam Sheriff, Ruben Seroussi, and Tzvi Avni. Written within the span of thirteen years, between 1985 and 1998, these works include Sherrif's (b. 1935) Mechaye Hametim ( He Who Revives the Dead, 1985); Seroussi's (b. 1959) A Victim from Terezin (1995; based on excerpts from Gonda Redlich's Terezin diary); Avni's (b. 1927) Se questo è un oumo (1998; a setting of poems by Primo Levi); and Avni's From There and Then (1994–1998). The compositions under discussion unfold a continuum of aesthetic approaches ranging from postromantic trajectories that stitch musical signs on nationalist teleological constellations (Sheriff), through conscious non-redemptive formulations (Seroussi), to compositional emphases on the migration and translocation of Jewish musics rather than affixed signs of otherness (Avni). The dilution of Jewish musical markers not only attests to the composers' abandoning of representational apparatuses, but also necessitates a broader look at the dialectical movement of Jewish musics before, during, and after the Holocaust, lest these sounds become objectified or otherwise overshadowed by nationalist constellations.